Pemanfaatan Kelapa Menjadi VCO Untuk Peningkatan Kesehatan - Samodra, Galih; Adita (LPPM Universitas Harapan Bangsa Purwokerto, 2024)
The Rempoah village community has abundant natural resources of coconuts. The use of coconuts is still very small, where the only parts used are the fruit and coconut water. In the pharmaceutical world, coconut oil traditionally produces a by-product in the form of coconut pulp which has low economic value. Therefore, efforts are needed to create alternative soap that utilizes local resources with the same benefits. This PkM activity aims to increase community knowledge and skills regarding the use of natural resources related to coconuts in the production of making soap from oil and coconut dregs. The problem solving solution offered is a participatory approach with counseling and training methods. Indicators of achieving the objectives of this activity are increasing community knowledge and skills and the availability of soap products. The results of this activity can increase the knowledge and skills of the Rempoah Village community in producing soap made from oil and coconut dregs by utilizing natural resources through training activities.